Studi Kontribusi Workplace Spirituality terhadap Employee Engagement Petugas Pemadam Kebakaran Kota Bandung - Rahmah Zakiyyatun Nufus; Ali Mubarak (UNISBA Press, 2022)
Abstract. Workplace spirituality is a study in industrial and organizational psychology with a focus on spiritual values in work. Employee engagement is an active role and a positive psychological state related to work which is operationalized by the intensity and direction of cognitive, emotional, and behavioral energy. Aim of this study to determine the description and contribution of workplace spirituality to employee engagement of firefighters in Bandung city. The hypothesis of this research is that workplace spirituality has a contribution to employee engagement of firefighters in Bandung. The method used in this study is a quantitative method using multiple regression data analysis. Workplace spirituality is measured by a measuring tool developed by Ashmos and Duchon (2000), employee engagement is measured by the Employee Engagement Scale (EES) from Shuck et al. (2017). The results showed that 97.5% of firefighters had high workplace spirituality and 91.1% of firefighters had high employee engagement. Simultaneously, workplace spirituality contributed 51.5% to employee engagement. Partially, the workplace spirituality factor that contributed the highest was the meaning at work factor with 9.32%, while the lowest was the blocks to spirituality factor which gave a negative contribution of 0.55% to employee engagement. Abstrak. Workplace spirituality merupakan kajian dalam psikologi industri dan organisasi dengan fokus terhadap spiritual values atau nilai-nilai spiritual dalam pekerjaan. Employee engagement merupakan peran aktif dan keadaan psikologis yang positif terkait pekerjaan yang dioperasionalkan oleh intensitas serta arah dari energi kognitif, emosional, dan perilaku. Penelitian ini bertujuan untuk mengetahui gambaran dan kontribusi workplace spirituality terhadap employee engagement petugas pemadam kebakaran Kota Bandung. Hipotesis penelitian ini adalah workplace spirituality memiliki kontribusi terhadap employee engagement petugas pemadam kebakaran Kota Bandung. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif dengan menggunakan analisis data regresi berganda. Workplace spirituality diukur dengan alat ukur yang dikembangkan oleh Ashmos dan Duchon (2000), employee engagement diukur dengan Employee Engagement Scale (EES) dari Shuck et al. (2017). Hasil penelitian menunjukkan 97.5% petugas memiliki workplace spirituality tinggi dan 91.1% petugas memiliki employee engagement tinggi. Secara simultan, workplace spirituality memberikan kontribusi sebesar 51.5% terhadap employee engagement. Secara parsial, faktor workplace spirituality yang memberikan kontribusi paling tinggi adalah faktor meaning at work sebesar 9.32%, sedangkan yang paling rendah adalah faktor blocks to spirituality yang memberikan kontribusi negatif sebesar 0.55% terhadap employee engagement.